Interv'iu s IUriem Levitanskim . Interv'iu s IUriem Levitanskim . Interview With IUrii Levitanskii . Интервью с Юрием Левитанским - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. A conversation about the creative work and life of the poet IUrii Levitanskii. Featured in the program: Levitanskii, IUrii Davidovich (Poet) Contributors: Riazanov, El'dar (Anchor) Беседа о творчестве и жизни поэта Юрия Левитанского. В программе участвуют: Левитанский, Юрий Давидович (Поэт) Создатели: Рязанов, Эльдар (Ведущий/Ведущая)